Analgesic effects of self-chosen music type on cold pressor-induced pain: Motivating vs. relaxing music. (September 2016) - Garcia, Rebecca L.; Hand, Christopher J.
The attenuation of perceived pain through exposure to music is known as music analgesia. The present study used a mixed-methods design, investigating whether self-chosen music moderated participants' psychological and physiological responses to pain during cold pressor (CP) tasks. Thirty participants took part (14 males, 16 females; M age = 27.77 years). Three levels of musical stimulation were employed—relaxing music, motivating music and a silent control condition. Dependent variables included: CP tolerance time, Profile of Mood score, visual analogue pain rating—intensity and unpleasantness (VAS-I & VAS-U), blood pressure and pulse rate. Qualitative semi-structured interviews further investigated perceived differences between musical stimulation types. Results demonstrated a significant effect of musical exposure on VAS-U scores [ F (2, 56) = 3.60, p = .034]. Pairwise comparisons revealed that VAS-U scores were significantly lower after exposure to relaxing music than after silence. Qualitative analyses of interview transcripts revealed dominant themes of distraction, absorption and context-dependent memory induction, with the most-preferred condition being motivational music. Results of the current study suggest that active listening to music reduces pain unpleasantness ratings, and that individual preference is an important determinant of the overall emotional and distraction properties of musical stimuli.